Indigenous themes and law 11.645/2008 in the context of an amazon public school in a decolonial reading (Research, Society and Development, 2022)
The purpose of this article is to discuss the indigenous theme and Law 11.645/2008 in the context of a public school in the Amazon. The study sought to understand and demonstrate how Law 11.645/2008, which provides for the inclusion of the study of Indigenous History and Culture in Basic Education curricula, is shown in the curricular discussions and practices developed by teachers of Elementary School I (1st to 5th Year) of a public school of the state education network in the city of Ji-Paraná - RO. As for the theoretical field, Cultural Studies and their possible articulations with the field of teacher training and other fields of knowledge production stand out. In order to think about culture and education, teacher training and school curriculum, we use the following authors: Bhabha, Hall, Bonin, Baniwa, Preto and Silva, among others who contributed to the understanding of the concepts of the researched theme. In methodological terms, the research is inspired by Bricolage by articulating strategic resources such as: interviews, mini-course and Discussion Group. The research showed the absence of teacher training in the area of ​​indigenous history and culture. There were attempts not to stereotype the indigenous people, however, the theme appears in teaching practices in specific ways, that is, on commemorative dates or when they appear in textbooks.